Effects of partial replacement of sugarcane silage with Moringa oleifera silage on carcass traits and meat quality of lambs - Gustavo Delmilho; Adibe Luiz Abdalla; Natana Mendes Marques; Theyson Duarte Maranhão; Vagner Ovani da Silva; Lumena Souza Takahashi; Leticia dos Santos Menezes; Mauro Sartori Bueno; Rafael Silvio Bonilha Pinheiro; Márcia Mayumi Harada Haguiwara; Ricardo Lopes Dias da Costa (Tropical Animal Health and Production, 2026)
Abstract This study evaluated the effects of partially replacing sugarcane silage with Moringa oleifera silage on carcass traits and meat quality of lambs. Sixteen male Santa Inês × Dorper lambs (23.0 ± 2.00 kg; 6 months old) were assigned to either sugarcane silage (C) or a mixed silage containing sugarcane and M. oleifera (C + M; 50:50 on a dry matter basis) over a 75-day experimental period, including 15 days of adaptation and 60 days of evaluation. Carcasses were evaluated for fasting weight, hot and cold carcass weights, carcass yields, non-carcass components, fat cover, ribeye area, and commercial cut yields. Meat quality was assessed in the Longissimus lumborum muscle for pH, lightness (L*), redness (a*), yellowness (b*), chroma (C*), hue angle (h°), cooking loss, shear force, proximate composition, and oxidative stability based on thiobarbituric acid reactive substances (TBARS). Lambs fed the C + M diet had lower fasting and hot carcass weights than those fed the control diet ( p < 0.01), whereas fat cover and ribeye area were not significantly affected. Meat dry matter, crude protein, ether extract, and ash contents did not differ between treatments ( p > 0.05). Color parameters, oxidative stability, and shear force were also unaffected by dietary treatment. Cooking loss was higher in the C + M group ( p < 0.05), indicating lower water-holding capacity under the evaluated conditions. Overall, replacing 50% of sugarcane silage with M. oleifera silage preserved most physicochemical meat quality attributes, although it reduced fasting and hot carcass weights and increased cooking loss. These findings indicate that M. oleifera silage may be used as an alternative forage resource in tropical lamb finishing systems, provided that its effects on carcass weight and water-holding capacity are considered.